Transcriptome analysis of genes involved in the pathogenesis mechanism of potato virus Y in potato cultivar YouJin - Yang, Tianqi; Zhao, Xingyue; Bai, Jinjiang; Lv, Wenxia; Chen, Qi; Hu, Jun; Liu, Guangjing; Zhao, Yuanzheng; Zhou, Hongyou; Zhao, Mingmin; Zheng, Hongli (Frontiers in Microbiology, 2024)
Introduction Potatoes (Solanum tuberosum L.) can be infected by various viruses, but out of all of viruses, the potato virus Y (PVY) is the most detrimental. Research shows that the potato cultivar YouJin is especially vulnerable to PVY and displays severe symptoms, including leaf vein chlorosis, curled leaf margins, large necrotic spots on the leaf blades, and the growth of small new leaves. Methods PVY infection in potato cultivar YouJin was confirmed through symptom observation, RT-PCR, and Western blot analysis. Transcriptome sequencing was used to analyze the genes associated with PVY pathogenesis in this cultivar. Result Transcriptome analysis of differential genes was conducted in this study to examine the pathogenesis of PVY on YouJin. The results showed that 1,949 genes were differentially regulated, including 853 upregulated genes and 1,096 downregulated genes. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis indicated that carbohydrate synthesis and metabolism pathways were suppressed, and electron transferase and hydrolase activities were reduced. Moreover, there were increased expression levels of protein kinase genes. By focusing on plant–pathogen interaction pathways, six core genes all upregulating the WARK family of transcription factors were obtained. Additionally, a constructed PPI network revealed the identification of key modular differential genes, such as downregulated photosynthesis-related protein genes and upregulated AP2/ERF-ERF transcription factors. Functional network enrichment analysis revealed that PVY infection limited RNA metabolism, glutathionylation, and peroxiredoxin activity while triggering the expression of associated defense genes in YouJin. After analyzing the above, 26 DEGs were screened and 12 DEGs were confirmed via RT-qPCR. Conclusion These results establish a hypothetical framework for clarifying the pathogenesis of PVY in the YouJin variety of potatoes, which will help design the disease resistance of YouJin.